Resource allocation for cellular device‐to‐device‐aided vehicle‐to‐everything networks with partial channel state information - Shan, Liqing; Wang, Michael Mao; Zhang, Fenghui; Chen, Shuaishuai; Zhang, Jingjing (Transactions on emerging telecommunications technologies, 2022)
In Vehicle‐to‐Everything (V2X), cellular Device‐to‐Device (D2D) communication can not only enhance system capacity and spectral utilization but also reduce the traffic load and communication delay. However, due to the fast variations of the channel state information (CSI) caused by high mobility of vehicles, the accurate CSI is difficult to be obtained in real‐time. In this paper, different from other previous researches that are subject to the perfect CSI, a more realistic channel state model is adopted that only the partial CSI of the communication links is available. Then we study the joint power allocation and spectrum sharing problem to maximize the total weighted ergodic capacity of all vehicular links, namely, Vehicle‐to‐Infrastructure (V2I) links and Vehicle‐to‐Vehicle (V2V) links. Meanwhile, the transmission reliability guarantees the quality of service (QoS) requirements of V2I and V2V. Since the formulated problem is a nonconvex mixed integer nonlinear programming (MINLP) problem, we first derive the strategy for obtaining the optimal solution of power allocation under arbitrary weighted factor and quantify different cases of feasible regions. Then we propose a two‐stage algorithm to complete the optimal resource allocation in polynomial time. Moreover, we further propose a low‐complexity spectrum sharing method based on the principles of Gale‐Shapley mechanism. The simulation results show that the proposed algorithms outperform the other baseline schemes significantly, and the low‐complexity scheme can effectively achieve a tradeoff between performance and complexity. V2X, aided with cellular D2D communication, has a great potential in enhancing the road safety and transportation. However, due to the fast variations of channel state information (CSI) caused by high mobility of vehicles, the accurate CSI is difficult to be obtained in real time. Therefore, we consider a more realistic channel state model that only partial CSI is available and propose the corresponding resource allocation scheme.